Respuesta :

Answer:

[tex]b=-\frac{-mx-2x+2m-60}{x};\quad \:x\ne \:0[/tex]

Step-by-step explanation:

Given the expression

[tex]\left(x-2\right)\left(x-m\right)=x^2-bx+60[/tex]

switch sides

[tex]x^2-bx+60=\left(x-2\right)\left(x-m\right)[/tex]

subtract x² from both sides

[tex]x^2-bx+60-x^2=\left(x-2\right)\left(x-m\right)-x^2[/tex]

simplify

[tex]-bx+60=-mx-2x+2m[/tex]

subtract 60 from both sides

[tex]-bx+60-60=-mx-2x+2m-60[/tex]

simplify

[tex]-bx=-mx-2x+2m-60[/tex]

subtract x from both sides;  x≠0

[tex]\frac{-bx}{-x}=-\frac{mx}{-x}-\frac{2x}{-x}+\frac{2m}{-x}-\frac{60}{-x};\quad \:x\ne \:0[/tex]

simplify

[tex]b=-\frac{-mx-2x+2m-60}{x};\quad \:x\ne \:0[/tex]

Thus,

[tex]b=-\frac{-mx-2x+2m-60}{x};\quad \:x\ne \:0[/tex]